Hegemony through the Architecture of the International Criminal Court - Baines, A. Michael (International Gramsci Journal, 2023)
This article links the buildings housing the International Criminal Court to the workings of that court by putting the Gramscian concept of hegemony to work. It considers occulted functions of the structure and subconscious aspects of the operations of the court. Gramsci’s hegemony is an articulation of a relationship of power between dominant and dominated classes. This relationship is not only one between consenting States and the court, but also between non-ratifying States and the court. It is also the locus of a power struggle between an elite judicial class and the sovereign ratifying States. The physical structure in which this international law is adjudicated and this struggle for power takes place, answers those criteria of hegemony as this article will demonstrate.